Folklore in the journal “Problems of Russian Literature” (1966–1991) - Dzyk, Roman; Shutiak, Lilia (TSU Shota Rustaveli Institute of Georgian Literature, 2020)
The journal “Problems of Russian Literature” is one of the oldest Ukrainian scientific periodicals on the problems of poetics and history of world literature. Since 1993, it has been published under the title “Problems of Literary Criticism”. Despite the fact that the main object for scientific studies in the journal is literature, the problems of folklore have always occupied an important place in it. In this article we will analyze only historical stage when the magazine was called “Problems of Russian Literature” (1966–1991). From time to time, there were columns devoted directly to folklore: “History of Soviet Folklore”, “History of Literary Studies and Folklore”, “History of Folklore”, “Folklore and Literature”, “Folklore”. In addition, the problems of folklore were covered in a large number of articles that were not included in these headings. Mostly folklore was analyzed in relation to the literature. Among the materials, there are both historical and theoretical studies. We reviewed all of these materials and tried to classify them.
Keywords: “Problems of Russian Literature”; “Problems of Literary Criticism”; folklore; folklore studies; literary historiography